The Genesis of La desesperanza by José Donoso - Mary Lusky Friedman (Studies in 20th & 21st Century Literature, 1999)
This study analyzes the seven hundred pages of working notes made by the Chilean writer José Donoso as he created La desesperanza, his 1986 novel about the return of a Chilean exile to his homeland. These notes, made in two sustained working sessions, one in the year beginning in December 1980 and the other in the first eight months of 1985, reveal a particular modus operandi: intent on inventing characters who were believable and complex, Donoso subordinated every other aspect of the work—plot, technical considerations like point of view and register, and even the ideas the novel would ultimately convey—to the imagining of a community of fully realized fictional beings. What is more, these working notes afford striking evidence that Donoso, in forging the novel, returned again and again, probably unconsciously, to the theme of ambivalence of child for parent and of parent for child. This theme, while discernible in the finished text, is far more visible in Donoso's ruminations about his work in progress. By examining the ways in which Donoso imbeds the theme of parent-child ambivalence in his text, and by relating his ways of doing so with Melanie Klein's notion of a small child's "split" image of a parent, this study identifies narrative strategies characteristic of Donoso's writing in general. The essay ends by suggesting that the theme of transformation of the self, central to all of Donoso's work, may well be an expression of this writer's preoccupation with ambivalence in the relationship between parent and child.
Keywords: la desesperanza; José Donoso; Chilean literature; exile; homeland; fiction; ambivalence; parent; child; narrative strategy; transformation; self; relationships